Gender norms and women’s economic resilience to climate change challenges: a case study of Ogun and Oyo states in Nigeria - Mudege, N.N.; Mdege, N.; Adeyeye, O.; Muzungaire, L.; Kakwasha, K. (2025)
This paper uses case studies of three agri-food systems in Nigeria – cassava, catfish and chicken – to demonstrate the impact of gender norms on women's economic resilience to climate change impacts. It provides insights into how transforming gender norms helps build economic resilience for women. It is based on data collected in Ogun and Oyo states through a stakeholders’ workshop, 55 Individual and Key Informant Interviews and 18 sex-disaggregated Focus Group Discussions. A gender-sensitive resilience approach was developed from literature on resilience approaches and gender transformative processes and used to analyse the data. The paper concludes that gender norms create gendered opportunities and constraints for economic resilience to the impacts of climate change. These opportunities and constraints emerge at the intersection of social institutions, agency and power relations. More men than women have access to and ownership of resources for economic resilience, such as land and finance. Men can often make long-term/strategic plans compared to women's short-term survival tactics. Approaches to promoting women’s economic resilience in climate change scenarios should challenge discriminatory gender norms and integrate gender-sensitive agricultural policies that encourage women’s equal and meaningful participation in all spheres, including at household, community, organizational and macro-environmental levels.